Physiological and Morphological Responses of Three Grapevine Rootstocks to Water Stress - Gholizadeh, Mojtaba; Hadadinezhad, Mahdi; Ebadi, Ali; Mohammadi Torkashvand, Ali (South African Journal of Enology and Viticulture, 2024)
Water deficit stress is one of the most frequent environmental stresses affecting the physiological and growth responses of plants, especially grapevines. However, grapevine varieties and species differ in their tolerance to water stress. To identify the most tolerant grapevine rootstock, a factorial randomised block design with two factors was used. The first factor included the susceptible cv. Sultana (V. vinifera L.) scion grafted onto three rootstocks (Yaghouti, Kolahdari and 140 Ru), and the second factor was water stress potential at three levels (control, -1 MPa and -2 MPa). The physiological parameters, such as malondialdehyde (MDA), electrical leakage (EL), proline, soluble sugar, protein, photosynthetic pigments, and antioxidant enzymes were investigated. Our results revealed that increasing water stress enhanced H2O2, MDA, EL, proline, soluble sugar, and soluble protein, while decreasing chlorophyll (Chl) and carotenoid contents, growth parameters, and plant dry weight. The glutathione peroxidase (GPX) activity was enhanced in response to water deficiency, whereas catalase (CAT) and ascorbate peroxidase (APX) enzymes exhibited higher activity at -1 MPa, which was then reduced under the lowest water potential (-2 MPa). In addition, 140 Ru rootstocks exposed to water stress had lower levels of MDA, H2O2, EL, and higher Chl (a, b), carotenoid, APX, and GPX activity, as well as higher shoot dry weight. Overall, the physiological and morphological responses of the three rootstocks propose that grafting the commercial Sultana cultivar onto drought-tolerant rootstocks such as 140 Ru is an effective strategy for improving drought stress tolerance.